METHODS OF FORMING THE ECOLOGICAL ATTITUDE OF STUDENTS ON THE SCIENCE OF BOTANY OUTSIDE THE CLASSROOM AT SCHOOL - Nazira Kengesbaeva (European Journal of Humanities and Educational Advancements, 2024)
In this article, it is explained that it is necessary to arouse students’ interest in biology and botany in school outside of school, to attract students to botanical circles outside of school, to familiarize them closely with the world of plants of the place where they grow up, to introduce them to the morphology and ecology of plants growing on the soil of their country.